Association between relative age effect and organisational practices of American youth football - Jones, C.; Visek, A.; Barron, M. J.; Hyman, M.; Chandran, A. (Journal of Sports Sciences, 2019)
The popular method of organising youth sport participants into age divisions, based solely on their birthdate, can result in an imbalance of the distribution of players. This is known as relative age effect (RAE), which inadvertently creates bias and is associated with deleterious short and long-term consequences. The overall purpose of this study was to examine how the potential for RAE is mitigated when simultaneously accounting for additional player criterion, supplementary to age. A mid-Atlantic American youth football registration database was acquired, including chronological (age), anthropometric (weight), and competency (skill) factors. Player (n = 1,265) data were classified into quartiles and multiple chi-square goodness of fit tests were conducted using proportions of live births as expected theoretical distribution values. When data were categorised by a single developmental criterion (e.g. age), results indicated significant departures (p = 0.002) from expected proportions. However, when categorised using multiple criteria (i.e. age, weight, and skill), equitable birthdate distributions were observed. Findings from this study indicate using only one developmental criterion for organising players is associated with RAE, whereas approaches accounting for multiple variables are not associated with RAE. This study provides youth football programs with early evidence for considering alternative methods of organising players.